2009
DOI: 10.1021/mp800157x
|View full text |Cite
|
Sign up to set email alerts
|

Controlling HBV Replication in Vivo by Intravenous Administration of Triggered PEGylated siRNA-Nanoparticles

Abstract: Harnessing RNA interference (RNAi) to inhibit hepatitis B virus (HBV) gene expression has promising application to therapy. Here we describe a new hepatotropic nontoxic lipid-based vector system that is used to deliver chemically unmodified small interfering RNA (siRNA) sequences to the liver. Anti HBV formulations were generated by condensation of siRNA (A component) with cationic liposomes (B component) to form AB core particles. These core particles incorporate an aminoxy cholesteryl lipid for convenient su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
116
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(119 citation statements)
references
References 40 publications
2
116
0
Order By: Relevance
“…In a similar manner, Carmona and colleagues developed liposomes composed of DOPE lipid and an aminoxy cholesteryl lipid, which enables attachment of biocompatible polymers, such as PEG (Carmona et al, 2009). This bioconjugation gives rise to oxime bonds, which are stable at neutral pH, but hydrolyzable at pH 5.5 and lower.…”
Section: Ph-sensitive Lipoplexesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar manner, Carmona and colleagues developed liposomes composed of DOPE lipid and an aminoxy cholesteryl lipid, which enables attachment of biocompatible polymers, such as PEG (Carmona et al, 2009). This bioconjugation gives rise to oxime bonds, which are stable at neutral pH, but hydrolyzable at pH 5.5 and lower.…”
Section: Ph-sensitive Lipoplexesmentioning
confidence: 99%
“…The delivery of siRNAs targeting hepatitis B virus sequences with lipid nanoparticles resulted in significant suppression of viral replication in mouse hepatocytes. In fact, siRNA-mediated silencing of HBV replication using these lipid carriers more effectively inhibited viral proliferation than treatment with lamivudine, a licensed HBV drug (Carmona et al, 2009). …”
Section: Ph-sensitive Lipoplexesmentioning
confidence: 99%
“…siRNA then dissociates from the complex and is released into the cytoplasm (Li and Szoka, 2007). Furthermore, it has been recently reported that fusogenic/synthetic peptides (Hatakeyama et al, 2009) or pH-sensitive moieties ( [Carmona et al, 2009] and [Akita et al, 2010]) can be attached to various polymers/lipids to assist endosomal escape. However, several studies have shown that multimerising peptides on the surface of the delivery vector cause immunogenicity following repeatedly intravenous administration ( [Schroeder et al, 2009] and [Shi et al, 2010]).…”
Section: Figurementioning
confidence: 99%
“…Intracellularly CDAN/DOPEsiRNA complexes appear to behave in a different fashion, accumulating in distinct but diffuse small non-lysosomal compartments for at least 5 h after transfection (Spagnou et al, 2004). Recently, a new hepatotropic nontoxic lipid-based vector system for delivering chemically unmodified siRNA to the liver to inhibit Hepatitis B virus (HBV) propagation was described (Carmona et al, 2008). These anti-HBV formulations were created based on synthetic, selfassembly ABCD nanoparticle paradigm (Kostarelos & Miller, 2005).…”
Section: Polycationic Lipidsmentioning
confidence: 99%
“…The resulting oxime linkages are robust at pH 7; however at a level of pH 5.5 and below, they are prone to decomposition. The developed vectors administered intravenously, efficiently deliver unmodified siRNAs to murine livers leading to the strong suppression of HBV replication (Carmona et al, 2008). The conjugates of guanidinium and cholesterol were synthesized with the yields of up to 61%, with the purpose of further improving the polar domain of cationic lipids (Vigneron et al, 1996).…”
Section: Polycationic Lipidsmentioning
confidence: 99%